A randomised clinical trial to determine the effect of a toothpaste containing enzymes and proteins on gum health over 3 months. (January 2019) - Daly, Sinéad; Seong, Joon; Newcombe, Robert; Davies, Maria; Nicholson, Julie; Edwards, Mark; West, Nicola
Abstract: Objectives: This study tested the efficacy of a toothpaste containing enzymes and proteins reflecting those naturally occurring in saliva which play an important role in maintaining bacterial balance to improve gingival health condition and reduce supra-gingival plaque formation over a period of 13 weeks as compared to a commercial control toothpaste. Methods: This study was a double-blind, randomised, parallel group, 3 month home use study in healthy volunteers. Non-smokers with a mean modified gingival index (MGI) score of between 2.00–2.75 and at least 20 natural teeth, a minimum of 5 teeth in each quadrant were enrolled in the study. At screening, participants underwent a dental prophylaxis and were issued with a standard fluoride toothpaste and toothbrush to use for 4 weeks. After 4 weeks, participants demonstrating ongoing eligibility were assessed for gingival health and plaque score and randomised to either test or control toothpaste, which they used at home twice daily. After 13 weeks, gingival health and plaque were re-scored. Results: 229 participants completed the study. There were no treatment associated adverse events. Plaque and gingival scores were significantly better in the test group as compared to the control group. Furthermore, in the test group plaque and gingival scores fell, while those in the control group rose over the 13 week period. Conclusions: The test toothpaste containing enzymes and proteins demonstrated significant plaque and gingival benefit compared to the control toothpaste, and was well tolerated. Clinical significance: Toothbrushing with the test product derived from naturally occurring enzymes and proteins had a clinical adjunctive improvement on gingival health compared to brushing alone with a commercially available fluoride toothpaste.